Renal tubular function of the child with thalassemia major who received repeated blood trransfusion - Dany Hilmanto; Boed Sinai Singadipoera; Ponpon Ijradinata (Indonesian Pediatric Society, 1999)
A descriptive study was done from December 2 , 1994 to January 5,1995, at the Department of Child Health of Hasan Sadikin General Hospital Bandung. A total of 50 thalassemia major patients who bad received 5,000 ml or more of blood transfusions and never received desfenioxamine underwent a renal tubular function test using a radionuclide technique (l-123 Hippuran) to determine the effective renalplasmft flow (ERPF). The subjects were div:ided into two groups according to the amount of transfusion. Group A who received a total of 5,000 to 10,000 mL of blood transfusion consisted of 23 children (11 boys and 12 girls); group B, those who received a total of 10,000 ml or more of blood transfusion, consisted of 27 children (14 boys and 13 girls). The total average of blood transfused for group A and B were 7563.91 (1780.59) and 20,665.93 (6632.39) rnl, respectively. The ERPF of all subjects were below the normal standard. The average value of ERPF of group A and B were 205.78 (62 .08) and 214.09 (59.44) ml/minute/1.73 m2, respectively. The correlation between the total amount of blood transfusion and ERPF of the subjects was not significant (Group A had r=O.l63, p=0.458; Group B had r=0.084, p=0 .934).